Top 10 Downloads from ACM's Digital Library. (Communications of the ACM, 2006)
The article provides information about the ten most popular downloaded papers from the Association for Computing Machinery (ACM)'s Web site. A chart is provided of the ten papers that were downloaded in August 2006 along with the rank of the articles for the year. A separate chart provides information about the most popular courses, by month and by year, at the ACM Profession Development Center on the association's Web site. Among the topics in the top ten articles are: temporal workflow management systems; dbswitches; java tutorials and scene breaks.